Daily distribution of macronutrient intakes of professional soccer players from the English Premier League - Anderson, L.; Naughton, R. J.; Close, G. L.; Di Michele, R.; Morgans, R.; Drust, B.; Morton, J. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
The daily distribution of macronutrient intake can modulate aspects of training adaptations, performance and recovery. We therefore assessed the daily distribution of macronutrient intake (as assessed using food diaries supported by the remote food photographic method and 24-hr recalls) of professional soccer players (n = 6) of the English Premier League during a 7-day period consisting of two match days and five training days. On match days, average carbohydrate (CHO) content of the prematch (<1.5 g·kg-1 body mass) and postmatch (1 g·kg-1 body mass) meals (in recovery from an evening kick-off) were similar (p > .05) though such intakes were lower than contemporary guidelines considered optimal for prematch CHO intake and postmatch recovery. On training days, we observed a skewed and hierarchical approach (p < .05 for all comparisons) to protein feeding such that dinner (0.8 g·kg-1)>lunch (0.6 g·kg-1)>breakfast (0.3 g·kg-1)>evening snacks (0.1 g·kg-1). We conclude players may benefit from consuming greater amounts of CHO in both the prematch and postmatch meals so as to increase CHO availability and maximize rates of muscle glycogen resynthesis, respectively. Furthermore, attention should also be given to ensuring even daily distribution of protein intake so as to potentially promote components of training adaptation.